VISUAL RRESENTATION OF RIVER POLLUTION AND GLOBAL WARMING IN ENVIRONMENTAL ADVERTISMENT: BASED ON ROLAND BARTHES' THEORY - PURANTRA, FAQRIE ARHAM RAFSANJANI; Dwi Budi, Budiharto (Arty: Jurnal Seni Rupa, 2025)
This study explores the visual representation of river pollution and global warming in advertisements related to natural ecosystems, using Roland Barthes’ semiotic framework. It focuses on how visual signs, such as polluted water, industrial smoke, melting ice, and vulnerable human figures, construct layered meanings that extend beyond their literal appearances. Through denotation, connotation, and myth, these elements convey urgent environmental messages while embedding cultural narratives and emotional appeals. The environmental issues raised in these advertisements not only depict the impact of ecological destruction but also reflect the tension between destructive human activities and the need for ecological balance. Such visualizations demonstrate how visual media play a significant role in shaping public awareness of environmental issues and encouraging changes in attitudes toward the natural world. Using a qualitative descriptive method, this research analyzes selected digital campaigns to understand how advertisements build ecological awareness and construct the myth of restoring harmony between humans and nature, ultimately aiming to strengthen collective responsibility for environmental sustainability.